Question and Answers Forum

All Questions      Topic List

Differential Equation Questions

Previous in All Question      Next in All Question      

Previous in Differential Equation      Next in Differential Equation      

Question Number 115721 by bemath last updated on 28/Sep/20

(D^2 −6D+9)y = (e^(3x) /x^2 )

(D26D+9)y=e3xx2

Commented by mohammad17 last updated on 28/Sep/20

m^2 −6m+9=0⇒(m−3)^2 =0⇒m_1 =m_2 =3  Yc=c_1 e^(3x) +c_2 xe^(3x)     W(u_1 ,u_2 )= determinant (((e^(3x)      xe^(3x) )),((3e^(3x)     3xe^(3x) +e^(3x) )))=e^(6x) ≠0    W_1 = determinant (((0                   xe^(3x) )),(((e^(3x) /x^2 )       3xe^(3x) +e^(3x) )))=−(e^(6x) /x)    W_2 = determinant (((e^(3x)              0)),((3e^(3x)         (e^(3x) /x^2 ))))=(e^(6x) /x^2 )    V_1 =∫ (W_1 /W) dx=∫ −(1/x^2 )dx=(1/x)    V_2 =∫ (W_2 /W) dx=∫(1/x^2 )dx=−(1/x)    Yp=V_1 U_1 +V_2 U_2     Yp=(e^(3x) /x)−e^(3x)     Y=Yc+Yp    Y=c_1 e^(3x) +c_2 xe^(3x) +(e^(3x) /x)−e^(3x)     (m.o)

m26m+9=0(m3)2=0m1=m2=3Yc=c1e3x+c2xe3xW(u1,u2)=|e3xxe3x3e3x3xe3x+e3x|=e6x0W1=|0xe3xe3xx23xe3x+e3x|=e6xxW2=|e3x03e3xe3xx2|=e6xx2V1=W1Wdx=1x2dx=1xV2=W2Wdx=1x2dx=1xYp=V1U1+V2U2Yp=e3xxe3xY=Yc+YpY=c1e3x+c2xe3x+e3xxe3x(m.o)

Commented by mohammad17 last updated on 28/Sep/20

Yc=c_1 e^(3x) +c_2 xe^(3x)     Yp=e^(ax)  . (1/(f(D+a))) f(x)    Yp=e^(3x) (1/((D+3)^2 −6(D+3)+9)).((1/x^2 ))    Yp=e^(3x)  (1/D^2 )((1/x^2 ))⇒Yp=−e^(3x) (1/D)((1/x))    Yp=−e^(3x) lnx    Y=Yc+Yp    Y=c_1 e^(3x) +c_2 xe^(3x) −e^(3x) lnx

Yc=c1e3x+c2xe3xYp=eax.1f(D+a)f(x)Yp=e3x1(D+3)26(D+3)+9.(1x2)Yp=e3x1D2(1x2)Yp=e3x1D(1x)Yp=e3xlnxY=Yc+YpY=c1e3x+c2xe3xe3xlnx

Commented by bemath last updated on 28/Sep/20

gave kudos all master

gavekudosallmaster

Commented by mohammad17 last updated on 28/Sep/20

thank you sir

thankyousir

Answered by john santu last updated on 28/Sep/20

let y = e^(3x) .q → { ((Dy=e^(3x) (q′+3q))),((D^2 y=e^(3x) (q′′+6q′+9q))) :}  we obtain   e^(3x) (q′′+6q′+9q)−6.e^(3x) (q′+3q)+9e^(3x) q=(e^(3x) /x^2 )  which simplifies to   q′′ = (1/x^2 ) → ((d(dq))/dx) = (1/x^2 )  ∫ ((d(dq))/dx) = ∫ (1/x^2 ) ⇒ (dq/dx) = −(1/x) +C_1    ∫ dq = ∫ (−(1/x) +C_1 ) dx  →q = −ln ∣x∣ + C_1 x+C_2   ⇒(y/e^(3x) ) = −ln ∣x∣ + C_1 x+C_2   ⇒y = −e^(3x) .ln ∣x∣ + (C_1 x+C_2 ).e^(3x)

lety=e3x.q{Dy=e3x(q+3q)D2y=e3x(q+6q+9q)weobtaine3x(q+6q+9q)6.e3x(q+3q)+9e3xq=e3xx2whichsimplifiestoq=1x2d(dq)dx=1x2d(dq)dx=1x2dqdx=1x+C1dq=(1x+C1)dxq=lnx+C1x+C2ye3x=lnx+C1x+C2y=e3x.lnx+(C1x+C2).e3x

Answered by Bird last updated on 28/Sep/20

y′′−6y′ +9y =(e^(3x) /x^2 )  h→r^2 −6r +9=0 ⇒(r−3)^2  =0 ⇒  r=3 ⇒y_h =(ax+b)e^(3x)  =axe^(3x)  +be^(3x)   =au_1  +bu_2   W(u_1 ,u_2 )= determinant (((xe^(3x)        e^(3x) )),(((1+3x)e^(3x)    3e^(3x) )))  =3x e^(6x) −(1+3x)e^(6x)  =−e^(6x)  ≠0  W_1 = determinant (((o        e^(3x) )),(((e^(3x) /x^2 )      3e^(3x) )))=−(e^(6x) /x^2 )  W_2 = determinant (((xe^(3x)         0)),(((1+3x)e^(3x)    (e^(3x) /x^2 ))))=(e^(6x) /x)  v_1 =∫ (w_1 /w)dx =∫ −(e^(6x) /(x^2 (−e^(6x) )))  =∫ (dx/x^2 ) =−(1/x)  v_2 =∫ (w_2 /w)dx =∫ (e^(6x) /(−xe^(6x) ))dx  =−∫ (dx/x) =−ln∣x∣ ⇒  y_p =u_1 v_1  +u_2 v_2   =xe^(3x) (−(1/x)) −e^(3x) ln∣x∣  =−e^(3x) −e^(3x) ln∣x∣ ⇒the general  solution is  y =axe^(3x)  +be^(3x) −(1+ln∣x∣)e^(3x)   =(ax+b −1−ln∣x∣)e^(3x)

y6y+9y=e3xx2hr26r+9=0(r3)2=0r=3yh=(ax+b)e3x=axe3x+be3x=au1+bu2W(u1,u2)=|xe3xe3x(1+3x)e3x3e3x|=3xe6x(1+3x)e6x=e6x0W1=|oe3xe3xx23e3x|=e6xx2W2=|xe3x0(1+3x)e3xe3xx2|=e6xxv1=w1wdx=e6xx2(e6x)=dxx2=1xv2=w2wdx=e6xxe6xdx=dxx=lnxyp=u1v1+u2v2=xe3x(1x)e3xlnx=e3xe3xlnxthegeneralsolutionisy=axe3x+be3x(1+lnx)e3x=(ax+b1lnx)e3x

Terms of Service

Privacy Policy

Contact: info@tinkutara.com